Non-tropical fibrocalculous pancreatic diabetes: case reports and review of recent literature - Xia, Fang; Zhou, Weibin; Wang, Bin; Hu, Yongmei (Journal of international medical research, 2020)
Background Fibrocalculous pancreatic diabetes (FCPD), an uncommon form of secondary diabetes, is caused by chronic nonalcoholic calcific pancreatitis and primarily occurs in tropical countries. Objective To present our first-hand experiences in the diagnosis and management of FCPD in two patients from a non-tropical location. Case report Two male Chinese patients (29 and 32 years old) presented with poor insulin function, negative islet cell and glutamate decarboxylase antibodies, and no spontaneous ketosis or abdominal pain. A careful clinical assessment was made and the results were correlated with laboratory findings. Abdominal ultrasound and computed tomography scans further revealed pancreatic calcification, calculi, and pancreatic duct dilation. Differential diagnosis confirmed FCPD and excluded the potential misdiagnosis of type 2 diabetes mellitus. FCPD in these patients was managed with insulin and symptomatic treatment with close monitoring. At the time of submission of this report, the first patient was stable at his last follow-up, but the second had been re-hospitalized for worsening symptoms. Conclusion Early differential diagnosis of FCPD based on clinical examination and biochemical and radiological investigations, in tandem with insulin therapy, can help manage FCPD effectively.